Experimental study on mechanical behavior and response mechanism of triaxial loading-unloading drilling in impact coal under the effect of water content - Guang’an ZHU; Zihao XU; Huan LIU (Meitan kexue jishu, 2025)
Stronger burst tendency of coal seams and rich water in the roof are the key factors leading to the failure of drilling cuttings method in the Inner Mongolia Shaanxi mining area. This article takes the No.2 coal seam of waer-rich rock burst coal mine in the Binchang mining area as the research object, a triaxial loading-unloading drilling test was designed (moisture content of 0、2.7%、5.4% and 7.8%; stress levels of 36-46、48-58 and 60-70 MPa), to explore the mechanical behavior of coal drilling under different water content and stress states. From the perspective of coal weakening and coal powder bonding, preliminarily reveal the influence mechanism of water and stress on the rock burst risk evaluation by the drilling cuttings method. The results show that: ① Under the influence of water, the physical and mechanical parameters of coal mass undergo varying degrees of degradation, and the plastic softening coefficient has the greatest impact on the theoretical drilling amount; ② When the moisture content of coal mass is w≤2.7%, the influence of water on the amount of drill cuttings is minimal, and an increase in stress level brings the experimental drill cuttings amount closer to the theoretical value; When the moisture content of coal mass is w≥5.4%, the bonding effect of water on the amount of drilling cuttings is enhanced, under the conditions of high stress and high water content, the drilling cuttings decreased significantly; ③ Due to the physical and chemical interaction between coal particles and water，the radius of plastic zone around the borehole increases, and the deformation capacity of coal mass is enhanced. As the stress levels rise, the stress around the drilling hole increases, the energy inside the coal body accumulates, and the deformation intensifies, the combined action of the two increases the amount of cuttings in drill pipe cutting; ④ In the range of water content less than 25%, as the water content increases, the increase of the liquid bridge force between the pulverized coal particles promotes the agglomeration and adhesion in the drilling hole, which leads to the reduction of drilling cuttings. The research results can provide an important theoretical basis for the evaluation of rock burst risk by drilling cuttings method in the rich water rock burst coal mine in Inner Mongolia and the Shaanxi mining area.